The Call for Environmentally-Based Language Teaching and Green Pedagogy: Climate Actions in Language Education - Nur, Sahril; Anas, Ismail; Pilu, Reski (Universitas Lancang Kuning, 2022)
Environmental education (EE) is one of the content-based language learning pedagogies used to enhance students’ awareness of environmental concerns and their effect on people and animals. It aims to build the language teachers’ and students’ awareness of the importance of EE and green pedagogy in ELT. However, research into integrating EE in language education is still scarce. Therefore, this article presents an analysis of multimodal discourse of the EE imperatives in using content and language integrated learning (CLIL) strategy. Grounded in the video data analysis (VDA) approach, the researchers analysed the recorded talks of two university lecturers who offered their finest teaching approaches, and two environmentalists from “Bye-Bye Plastic Bags Jakarta” who described their significant efforts in handling plastic waste from a 2021 webinar held by the British Council Indonesia. Based on the thematic analysis, the forum suggests: 1) including environmental issues in language curriculum, syllabus, and textbook development, 2) providing environmentally-relevant materials and resources, 3) providing environmental language teacher professional development, and 4) accelerating environmental literacy programs at all levels of education. In other words, the inclusion of green pedagogy and environmental sustainability initiatives in ELT should be well-acknowledged. The methodological and pedagogical strategies in integrating environmental issues in ELT in this study addressed the high demand to catalyse language teachers’ metacognitive awareness in EE and indirectly build students’ metacognitive skills about environmental care.